Gd3 Triangles in a Polyoxometalate Matrix: Tuning Molecular Magnetocaloric Effects in Gd30M8 Polyoxometalate/Cluster Hybrids Through Variation of M2+. Issue 10 (31st July 2021) - Ibrahim, Masooma; Peng, Yan; Moreno-Pineda, Eufemio; Anson, Christopher E.; Schnack, Jürgen; Powell, Annie K.
Abstract : The syntheses and structures of a family of five new Ln/3d cluster containing polyoxometalates (POMs) [{(GeW9 O34 )2 Ln III 3 (CO3 )(OH2 )3 }6 {3M II 2 Ln III 3 (μ3 ‐OH)6 (OH2 )6 }4 ] 50− Ln30 M8 , where Ln = Gd or Y, and M = Zn, Mn, Co, are presented. This structural motif of a giant tetrahedron contains Ln III 3 and M II 2 Ln III 3 ‐cluster units which are well‐isolated within the diamagnetic polyoxotungstate system. The magnetic properties of Gd30 Mn8 , Y30 Mn8 and Gd30 Zn8 can be successfully modeled using a Heisenberg approach. Investigation of their magnetocaloric effect (MCE) reveals that this can be tuned through variation of the 3d metal ion. This is the first such systematic study on heterometallic 3d‐4f‐ POM clusters. The Gd30 Zn8 analogue illustrates a promising way forward to magnetic cooling at sub‐Kelvin temperatures. Abstract : A family of nanoscale heterometallic 3d–Gd III and Gd III ‐containing polyoxometalates (POMs), which feature weakly antiferromagnetically coupled Gd III 3 triangles dispersed in a POM matrix, allows tuning of the magnetocaloric effect by variation of the 3d cation, and provide a route for the development of low‐temperature magnetic refrigerants.